Validation of Two Questionnaires Assessing Nurses' Perspectives on Addressing Psychological, Social, and Spiritual Challenges in Palliative Care Patients - Vesna Antičević; Ana Ćurković; Linda Lušić Kalcina (MDPI AG, 2024)
Background: Palliative care provides holistic support, addressing physical, psychological, social, emotional, and spiritual dimensions of suffering, known as "total pain", to improve patients' quality of life. Patients often rely on healthcare professionals, particularly nurses, for support. This study aimed to develop and validate questionnaires assessing nurses' perceptions of psychological, social, and spiritual issues in palliative care and their effectiveness in managing them. Methods: Two self-rated questionnaires were created: the Psychological, Social, and Spiritual Problems of Palliative Patients' Questionnaire and the Effectiveness in Coping with the Psychological, Social, and Spiritual Challenges of Palliative Care Patients. The study surveyed 237 nurses caring for palliative patients in Split Dalmatian County, Croatia. Results: The questionnaires demonstrated high reliability with Cronbach's α values of 0.98 and 0.99. Factor analysis revealed four factors for the first questionnaire and three for the second. Nurses primarily perceived patients as experiencing fear and emotional/spiritual suffering, with the greatest difficulty coping with the fear of the disease outcomes. Nurses acknowledged the need for improvement in addressing patient challenges, highlighting gaps in the Croatian system. Conclusions: Ongoing efforts are crucial to prioritize palliative care globally, with nursing professionals playing a vital role in symptom management.